Correlation studies on structurally diverse porphyrin monomers, dimers and trimers and their nonlinear optical responses - SENGE, MATHIAS; WANG, JUN; BLAU, WERNER (My University, 2009)
An investigation of the nonlinear absorption of a wide range of structurally diverse porphyrin monomers, bisporphyrins and trisporphyrins, using open Z-scan technique with 6 ns pulsed laser operating at 532 nm was carried out. Using the theory of reverse saturable absorption, the intensity dependent nonlinear absorption coefficient ?eff was deduced from the experiments. Monomers which Soret band maximum was situated closer to the experimental wavelength had higher ?eff. The ?eff of dimers and trimers were in the same range as for monomers. The highest ?eff = 5.3 10-8 cmW-1 was found for a zinc complex of 5,15-A2B2 type porphyrins with 3-methoxyphenyl and trimethylsilyl-ethynyl groups in the meso positions.
PUBLISHED
Keywords: Chemistry